Prevalence and Associated Factors of Depressive Symptoms Among Patients With Chronic Low Back Pain: A Cross-Sectional Study - Hu, Yueming; Yang, Zechuan; Li, Yong; Xu, Yong; Tian, Mengge; Jiang, Nan; Guo, Ningfeng (Frontiers in Psychiatry, 2022)
Background: Few studies have focused on depressive symptoms among patients with chronic low back pain in China. The aim of this cross-sectional study was to assess the prevalence and associated factors of depressive symptoms in patients with chronic low back pain. Methods: From May to August 2021, 1172 patients with chronic low back pain were recruited in China. Depressive symptoms were assessed through the Patient Health Questionnaire. Associations of demographic characteristics, clinical characters and social-psychological factors with depressive symptoms were investigated among patients with chronic low back pain. Results: The prevalence of depressive symptoms was 25.00%. Logistic regression analysis found that duration of pain in 1 to 5 years (1 to 3 years: OR = 2.91, 95%CI: 1.65-5.14, 3 to 5 years: OR =3.09, 95%CI: 1.55-6.15) and more severe pain (OR = 1.13, 95%CI: 1.10-1.17) were associated with higher risks of depressive symptoms. Better family function (good family function: OR = 0.25, 95%CI: 0.15-0.41, moderate family dysfunction: OR = 0.47, 95%CI: 0.29-0.77) and higher pain self-efficacy (OR = 0.94, 95%CI: 0.93-0.95) were associated with lower risks of depressive symptoms. Conclusion: Patients with chronic low back pain have a high prevalence of depressive symptoms in China. Duration of pain, pain severity, family function and pain self-efficacy were predictors of depressive symptoms among chronic low back patients in China. Early identification of the associated factors may be helpful for the timely management of depressive symptoms.